Biotransformation of ethyl p-methoxycinnamate from Kaempferia galanga linn using Aspergillus Niger - Nor Hazwani binti Mohd Hasali (Kullliyyah of Science, International Islamic University Malaysia, 2014)
Studies were carried out on the extract of Kaempferia galanga Linn rhizome obtained using steam distillation and supercritical fluid extraction (SFE). After purification, a major compound of the K. galanga Linn extract, ethyl p-methoxycinnamate (EPMC) was confirmed by UV, FTIR, GC/MS and NMR spectrometry. Biotransformation of EPMC using Aspergillus niger resulted in production of ethyl p-hydroxycinnamate (EPHC) based on spectroscopy data. The biological activity of EPMC and transformed product was established by antimicrobial and anticancer assays. EPHC was active against all strains tested with a good minimum inhibitory concentration (MIC) value against S. aureus (MIC=333.3μg/mL), B. cereus (MIC=333.3μg/mL), P. aeruginosa (MIC=111.1μg/mL), E. coli (MIC=111.1μg/mL) and C. albican (MIC=111.1μg/mL) while EPMC exhibited less growth inhibition potential. EPHC has shown minimum bactericidal (MBC) concentration toward B. cereus, P. aeruginosa, E. coli and C. albicans except S. aureus at the concentration of 1000 μg/mL while EPMC did not show killing potential toward the tested microorganisms in this study. The cytotoxicity of the natural products was assessed on human breast cancer (MCF-7) and non-small lung carcinoma (H1299) cell lines using MTT [3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide]assays. EPHC was the most cytotoxic at 1000 μg/mL against human breast cancer (MCF-7) and non-small lung carcinoma (H1299) cell lines with the percentage cell viability of 9.87% and 13.01%, respectively while the IC50 were 340 μg/mL and 560μg/mL, respectively. EPHC showed slight improvement in cytotoxicity activity as compared to EPMC. This is the first report on the biotransformation of ethyl p-methoxycinnamate by Aspergillus niger and evaluation of the biological activities of the biotransformed products.